2020
DOI: 10.21203/rs.3.rs-44755/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal Health Care Service Utilization Among Young Married Women in India, 1992-2016: Trends and Determinants

Abstract: Background: Utilizing maternal health care services can reduce a substantial proportion of maternal mortality. Maternal deaths among young women (15-24 years) shares 38% of total maternal mortality in India. However, there is a paucity of studies focusing on the maternity care needs of young women. This paper therefore aimed to examine the trends and determinants of full antenatal care (ANC) and skilled birth attendance (SBA) utilization among young married women in India.Methods: The study analysed data from … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 52 publications
3
12
0
Order By: Relevance
“…A total of 16 explanatory variables were included in the study. These variables were selected because of their association with the outcome variables from previous studies [ 28 , 29 , 31 33 ] as wells as their availability in the DHS dataset. The variables were further grouped in to individual level and household/community (contextual) level.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 16 explanatory variables were included in the study. These variables were selected because of their association with the outcome variables from previous studies [ 28 , 29 , 31 33 ] as wells as their availability in the DHS dataset. The variables were further grouped in to individual level and household/community (contextual) level.…”
Section: Methodsmentioning
confidence: 99%
“…We, therefore, used the dichotomised responses in the final analysis. The coding and classification were informed by literature that used the DHS data sets 34–37…”
Section: Methodsmentioning
confidence: 99%
“…Also, in Uttar Pradesh, India, women’s age at marriage in addition to religion moderated the effects of literacy and wealth on facility delivery [ 33 ]. However, some studies showed that age at first marriage and childbearing had no association with antenatal care utilisation [ 34 , 35 ] while other studies showed increased antenatal care use and early booking among younger mothers [ 36 , 37 ]. This thus shows a lack of consensus in the literature regarding the relationship between age at marriage and antenatal care use.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%